A Lightweight BT-Based Authentication Scheme for Illegal Signatures Identification in VANETs - Eko Fajar Cahyadi; Min-Shiang Hwang (IEEE Access, 2022)
Research related to vehicular ad hoc networks (VANETs) has received significant attention in recent years. Despite all the advantages, the security and privacy in VANETs still become the main challenge that is widely open to discussion. The authentication scheme plays a substantial role to guarantee the security and privacy of information circulation and verification efficiency in VANETs. In this high-density environment, a scalability issue would emerge when the number of message-signature pairs received by a roadside unit (RSU) or vehicles becomes large. This issue happens because those entities cannot sequentially verify each received signature according to the required time limit. Researchers believe that the symmetric cryptography-based authentication scheme provides a lightweight verification operation, which leads to low computation cost. Combined with the batch verification process, this approach can be beneficial. However, to the best of our knowledge, not many of those related schemes provide a realistic scenario regarding illegal signatures’ appearance. Could the system identify the forged messages? Is it still efficient enough to do such an operation? In this paper, we propose a lightweight binary tree-based (BT-based) authentication scheme with a batch verification mechanism, that could efficiently identify a modest amount of illegal signatures in the sum of messages. To even improve the operation, we combine our BT-based batch verification scheme with our vehicle reputation scoring system. By this approach, we can guarantee the best-case scenario (the most desirable condition) in our BT-based identification appear as much as possible. Hence, the computation cost can be kept low.